Late Cenozoic fire enhancement response to aridification in mid-latitude Asia: Evidence from microcharcoal records. (1st May 2016) - Miao, Yunfa; Fang, Xiaomin; Song, Chunhui; Yan, Xiaoli; Zhang, Ping; Meng, Qingquan; Li, Fang; Wu, Fuli; Yang, Shengli; Kang, Shuyuan; Wang, Yuanping
Abstract: Fire provides an important indicator of paleoclimatic change. However, little information relating to late Cenozoic fire history has been gathered in mid-latitude Asia (including Inner Asia and East Asia), a key region for understanding the development of the arid-monsoon climate system as well as the driving forces behind it. Here we first report the records of microcharcoal concentrations (MC) covering the Holocene (10–0 ka) and late Pleistocene (0.8–0 Ma), which we use to analyze the fire activity patterns at an orbital time scale; then we compile the late Cenozoic MC record to investigate the long-term fire history by analyzing four cores from the Yangtze River Delta (YRD) area, East Asia (representing 8–0 Ma) and three sites in Inner Asia (representing 18–2 Ma). The results show that the (i) MC remained higher during the relatively dry late Holocene/glacial stages than that during the humid middle Holocene/interglacial stages at individual sites; (ii) MC increased with time in both Inner Asia and East Asia after 18 and 8 Ma, respectively; and (iii) MC always remained higher in the dry Inner Asia than in the contemporaneous wet East Asia. All these characteristics imply that late Cenozoic fire occurrence in mid-latitude Asia experienced a gradual increasing trend along with the global temperature/ice volume change, and indicates a continuous aridification trend across mid-latitude Asia. The global cooling, rather than the Tibetan Plateau uplift, might have played a key role in this observed trend. Graphical abstract: Highlights: Little information about late Cenozoic fire has been gathered in mid-latitude Asia. Microcharcoal concentrations (MC) are crucial to study fire activity. Fire activity at Holocene/orbital time scales is linked with the precipitation. Increasing fire trends in late Cenozoic are well correlated with the aridification. Global cooling, rather than Tibetan Plateau uplift plays a key role in fire trends.